Interconnection Systems as An Alternative Fulfillment of Women and Children Right Post Court Verdict - Naim, Abdul Haris (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
After the divorce decision was made by the court, the problem of difficult execution regarding the fulfillment of women's and children's rights arose. This research discusses alternatives after the decision of the Religious Court in adjudicating divorce cases to ensure the fulfillment of women's rights after divorce. The method in this research was carried out using a type of literature. The data was collected through an inventory of related laws and regulations, and through books, journals and other secondary materials related to the research focus.  The results of this research offer an alternative interconnection system between institutions that is solution-oriented by utilizing and improving existing cooperation in the Religious Courts to optimize mut'ah (contract) and hadlanah (children fulfillment) payments from ex-husbands to ex-wives after divorce.  In this way, the implementation of religious court decisions regarding women's rights after divorce can be carried out effectively.